Benefit of combining quantitative cardiac CT parameters with troponin I for predicting right ventricular dysfunction and adverse clinical events in patients with acute pulmonary embolism - Meyer, Mathias; Fink, Christian; Röger, Susanne; Apfaltrer, Paul; Haghi, Dariusch; Kaminski, Wolfgang E.; Neumaier, Michael; Schönberg, Stefan; Henzler, Thomas (European journal of radiology, 2012)
Objective To prospectively evaluate the diagnostic accuracy of quantitative cardiac CT parameters alone and in combination with troponin I for the assessment of right ventricular dysfunction (RVD) and adverse clinical events in patients with acute pulmonary embolism (PE). Materials and results: This prospective study had institutional review board approval and was HIPAA compliant. In total 83 patients with confirmed PE underwent echocardiography and troponin I serum level measurements within 24h. Three established cardiac CT measurements for the assessment of RVD were obtained (RV/LVaxial, RV/LV4-CH, and RV/LVvolume). CT measurements and troponin I serum levels were correlated with RVD found on echocardiography and adverse clinical events according to Management Strategies and Prognosis in Pulmonary Embolism Trial-3 (MAPPET-3 criteria. 31 of 83 patients with PE had RVD on echocardiography and 39 of 83 patients had adverse clinical events. A RV/LVvolume ratio>1.43 showed the highest area under the curve (AUC) (0.65) for the prediction of adverse clinical events when compared to RV/LVaxial, RV/LV4Ch and troponin I. The AUC for the detection of RVD of RV/LVaxial, RV/LV4Ch, RV/LVvolume, and troponin I were 0.86, 0.86, 0.92, and 0.69, respectively. Combination of RV/LVaxial, RV/LV4Ch, RV/LVvolume with troponin I increased the AUC to 0.87, 0.87 and 0.93, respectively. Conclusion: A combination of cardiac CT parameters and troponin I measurements improves the diagnostic accuracy for detecting RVD and predicting adverse clinical events if compared to either test alone.
Gesehen am 20.11.2018